2017
DOI: 10.1002/bdr2.1132
|View full text |Cite
|
Sign up to set email alerts
|

Species Comparison of Postnatal Development of the Female Reproductive System

Abstract: The postnatal development of the female reproductive system in laboratory animals and humans is reviewed. To enable a meaningful species comparison of the developing female reproductive system, common definitions of developmental processes were established with a focus made on aspects that are similar across species. A species comparison of the key endocrine, morphologic, and functional (onset of ovarian cycles and ability to reproduce) features of postnatal development of the female reproductive system is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 163 publications
(190 reference statements)
2
21
0
Order By: Relevance
“…The present study first showed that adolescent female Sprague-Dawley rats undergo puberty throughout P35-38, with 31% of P35 rats not having begun estrous cycling. This is consistent with previous research (Goldman, Laws, Balchak, Cooper, & Kavlock, 2000;Laffan et al, 2018). For adolescent females, the cycle was somewhat irregular (Figure 1c).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study first showed that adolescent female Sprague-Dawley rats undergo puberty throughout P35-38, with 31% of P35 rats not having begun estrous cycling. This is consistent with previous research (Goldman, Laws, Balchak, Cooper, & Kavlock, 2000;Laffan et al, 2018). For adolescent females, the cycle was somewhat irregular (Figure 1c).…”
Section: Discussionsupporting
confidence: 93%
“…For adolescent females, the cycle was somewhat irregular (Figure 1c). This is also consistent with previous research reporting that for many mammalian species, including rats, the first few menstrual cycles are typically irregular (reviewed in Goldman et al, 2000;Laffan et al, 2018). Secondly, estrous phase during extinction significantly affected conditioned freezing in female adolescent rats.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, preference for a threshold-level drug-paired context may be driven by MSinduced TNF signaling specifically in males, since females show neither changes in TNF expression nor preference for a cocaine-paired chamber. While the female adolescents investigated here had not yet reached an age of sexual maturation and reliable ovarian cycling (Laffan et al, 2018), it remains possible that the sex-specific impact of MS on CPP was impacted by gonadal hormones. Since estradiol and progesterone have all been reported to influence drug-seeking behavior (e.g., (Lynch, 2008), it wil be important in future studies to determine the interactive effects of early life experience, sex hormones, and immune signals on CPP and other addiction-related behaviors.…”
Section: Discussionmentioning
confidence: 97%
“…A second set of review articles (Ridings, 2018) was published which corroborates the recommendation that PND 4 in the rodent is generally similar to a term infant. Postnatal reviews were published on the eye (Van Cruchten et al, 2017), lung (Lewin & Hurtt, 2017), kidney (Frazier, 2017), male (Picut, Ziejewski, & Stanislaus, 2017) and female reproductive tracts (Laffan, Posobiec, Uhl, & Vidal, 2018), the gastrointestinal tract (Downes, 2018) and the ear (Powles‐Glover & Maconochie, 2018). There are also publications on the developing immune system (Holsapple, West, & Landreth, 2003; Kuper et al, 2016; Skaggs et al, 2019) and the CNS (Semple, Blomgren, Gimlin, Ferriero, & Noble‐Haeusslein, 2013; Wood, Beyer, & Cappon, 2003).…”
Section: Approach To Juvenile Rodent Studies—tolerability Phasementioning
confidence: 99%